Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. Mitra Usaha Flores - Elmaria Nona Elsi; Maria Silvana Mariabel Carcia; Margaretha Yulianti (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This research aimed to investigate the impact of ledearship and organizational culture on employee performance at PT. Mitra Usaha Flores. The research focused on understading the relationship between employee performance, leadership, and organizational culture. The objectives were to: 1) describe employee performance leadership, and organizational culture, and 2) analyze the influence of leadership and organizational culture employee performance, both individually and collectively. The research included 90 employees as as to population, with 48 respondents selected using simple random sampling and the Slovin formula. Data was collected via questionnaires and analyzed using descriptive methods and multiple linear reggresion for inferential statistics. Hypothesis testing was conducted using the F-test an t-test. The descriptive analysis results indicated that the Employee Performance and Leadership variabels meet the criteria for good performance, as does the Organasitional Culture variabel. According to the t-test, the leadership variabel had a partial effect on Employee Performance, whiel the Organizational Culture variabel did not. The F-test results showed that neither the Leadership nor the Organizational Culture variabels had a significant simultaneous effect on Empoyee Performance. The determination analysis indicated that the two independent variabels in the study explaint a 2,7 % fluctuation of Employee Performance at PT. Mitra Usaha Flores.